PROFIL PENGOBATAN PENYAKIT HIPERTENSI PADA PASIEN RAWAT INAP RUMAH SAKIT UMUM DAERAH LABUANG BAJI PERIODE JANUARI-APRIL 2023 - Sukmawati, Sukmawati; Husain, Quflun Amalia; Asmaliani, Ira (As-Syifaa Jurnal Farmasi, 2025)
Labuang Baji Regional General Hospital in Makassar provides services for hypertension, including consultation, treatment, and monitoring of patients with hypertension. Hypertension management can be done with antihypertensive drugs, which must be used rationally to achieve target blood pressure and reduce the risk of cardiovascular complications. This study aims to analyze the profile of antihypertensive drug use in terms of correct indication, correct drug, correct dose, and correct dosing interval in inpatients at Labuang Baji Regional General Hospital. This study uses a quantitative method with a descriptive non-experimental research type with data collection carried out retrospectively from patient medical record data from January to April 2023 with a sample size of 50 people. The results of the study showed that the level of rational compliance was high where the results of the evaluation of the use of antihypertensive drugs were based on the right indication 100%, the right drug 98%, the right dose 94%, and the right time interval of administration 94%. Thus, the rational use of antihypertensive drugs is needed to achieve clinical outcomes to improve the quality of life of patients.